A novel sensor design for the tyre load monitoring: overall design and analysis. (1st January 2011) - Kamalzadeh, Amin; Golnaraghi, M. Farid; Parameswaran, Ash M.; Leung, Albert M.
The growing demand for safety, comfort, and ride performance in the automotive industry motivates the design of advanced sensory systems. In this work, a sensory system is designed which measures the wheel forces and moments in every direction. The design benefits from a compact configuration by only modifying one part of the vehicle's current wheel assembly. The forces and moments are measured using the deflections of a flexible cylindrical layer embedded in the external hub of the wheel bearing assembly, where all the loads transmit through.